PROVERB AS AN OBJECT OF PHILOLOGICAL RESEARCH - Khamraeva Guli Nurmakhmatovna (Galaxy International Interdisciplinary Research Journal, 2022)
The relationship of paremic genres has not been studied in a complex way. Linguoculturology is the study of the interconnectedness of language and culture, with proverbs at the center. Proverbs reflect the people’s historical experience and past. Proverbs are studied semantically in folklore and linguistics. Proverbs are studied on the basis of linguistic achievements under the name of semantic integrity. In particular, the research of M.Z. Sadriddinova is devoted to the study of the vocabulary of Uzbek proverbs and sayings.